Significados do trabalho coletivo no processo de formação inicial de docentes em Educação Matemática digital - Carvalho, Alex Medeiros de (2009)
The aim of this search is to understand the meaning of teamwork in Digital Mathematics for Teachers initial training processes. In the project based upon a working group formation, the main challenge in a Supervised Probation course was to find methods for teachers initial formation, which could involve them in collaborative practices within the schools. This could produce and improve socializing moments and professors knowledge as related to Mathematics and Communication and Information Technologies (CIT) in school. Based on historical and cultural aspects of these undergraduates, which has influence in their professional training during supervised probation, we were able to undertake some reflective discussions concerned to the implications of Initial Empowerment process of Digital Mathematics Education professors in their future professional work. Finally, we understood how important practices derived from knowledge systematization is and we point out as a contribution of this search that we need further investigation on teamwork proposals.